Clinical performance of two commercially available rapid antigen tests for influenza, RSV, and SARS-CoV-2 diagnostics - Laura E. Savolainen; Joanna Peltola; Risto Hilla; Tapio Åman; Markku Broas; Ilkka S. Junttila (Microbiology Spectrum)
ABSTRACT Rapid antigen tests (RATs) might provide rapid, low-cost, and easy-to-perform choice to nucleic-acid amplification methods (NAAT) in point-of-care (POC) diagnostics of respiratory infections. The clinical performance of two commercial combo-RATs for influenza A and B, respiratory syncytial virus (RSV) and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) POC diagnostics, was assessed. RAT and real-time-PCR (RT-PCR) analysis were performed on 620 patients admitted to the emergency department due to respiratory symptoms. The sensitivity and specificity of the RATs compared with RT-PCR results were studied. The sensitivity of the RATs with respect to symptom duration was also estimated. The tested RAT1 showed sensitivities of 98.68%, 73,53%, and 44.44% for SARS-CoV-2, influenza A, and RSV, respectively, when the cycle threshold (Ct) values were <25 and 95.45%, 68.42%, 40.0% with Ct values <30. In RAT2 analysis, respective sensitivities for influenza A and RSV in samples with Ct <25 were 85% and 100% and in samples with Ct <30 respective sensitivities dropped to 69.23% and 66.67%. Positive SARS-CoV-2 cases during the RAT2 testing period and influenza B cases during both the RAT1 and RAT2 testing periods were scarce, so they were omitted from the statistical analysis. The specificity of both tested RATs was high and varied between 99.48% and 100%. The clinical use of RATs should be carefully considered due to the possibility of insufficient sensitivity. Because the specificity of the tests is high, the use of such tests might provide added value, for example, in emergency units, particularly when the prevalence of these infections is high. However, an option to confirm negative RAT by NAAT should be available.IMPORTANCERapid diagnostics of respiratory viruses is essential for clinical management, infection control, and epidemiological surveillance. Our results showed that due to the high specificity and still inadequate sensitivity, rapid antigen tests (RATs) might be useful for influenza, respiratory syncytial virus, and severe acute respiratory syndrome coronavirus 2 point-of-care diagnostics when correctly used. The results provide useful information for laboratory and infectious disease control professionals to support decision-making when implementation of the RATs in clinical use is planned.